A comprehensive simulation of gas concentration impedance for solid oxide fuel cell anodes. (December 2015) - Fadaei, M.; Mohammadi, R.
Highlights: The simulated concentration impedance spectra show two dominant features; a high-frequency arc and a low-frequency arc. That convective transport plays an important role on the concentration impedance. The porous electrode with porosity of 0.3 is negligible for the anode thickness less than 30 μm. Gas concentration resistance decreases with increased inflow velocity. Abstract: This paper presents electrochemical impedance simulation of a solid oxide fuel cell anode. The model takes in to account the gas-phase transport processes both in the gas channel and within the porous electrode and couples the gas transport processes with the electrochemical kinetics. The gas phase mass transport is modeled using the transient conservation equations (mass, momentum and species equations) and Butler–Volmer equation is used for the anode electrochemistry. In order to solve the system of non linear equations, an in-house code based on the finite volume method is developed and utilized. Results show a depressed semicircle in the Nyquist plot, which originates from gas transport processes in the gas channel, in addition to a Warburg diffusion impedance originates from gas transport in the thick porous anode. The simulation results are in good agreement with published experimental data.